2021
DOI: 10.1101/2021.03.17.434993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic plasticity within the EMT spectrum, rather than static mesenchymal traits, drives tumor heterogeneity and metastatic progression of breast cancers

Abstract: The Epithelial-to-Mesenchymal Transition (EMT) is a developmental cellular program frequently coopted by cancer cells and is a key contributor to both heterogeneity in solid tumors and later stage chemo-resistance and metastasis. Rather than being a switch from an epithelial to a mesenchymal state, increasing evidence points to the existence of intermediate EMT states, wherein cells co-express both epithelial and mesenchymal traits. Multiple stable intermediate EMT states possessing unique characteristics exis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 84 publications
0
41
0
Order By: Relevance
“…Previous work establishing this model system has demonstrated that the intermediate clones represent a population of tumor cells with high tumor-initiating potential(8). We show high 5hmC CpGs association with motifs of key EMT transcription factors which may indicate recruitment of various transcription factors by 5hmC may be a potential mechanism regulating the intermediate clones' high tumor-initial potential.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…Previous work establishing this model system has demonstrated that the intermediate clones represent a population of tumor cells with high tumor-initiating potential(8). We show high 5hmC CpGs association with motifs of key EMT transcription factors which may indicate recruitment of various transcription factors by 5hmC may be a potential mechanism regulating the intermediate clones' high tumor-initial potential.…”
mentioning
confidence: 51%
“…To explore potential functional differences in gene regulation between intermediate and distal clones, we identi ed regions of accessible chromatin using ATAC-seq and conducted transcription factor motif enrichment analysis of accessible chromatin peaks containing at least one high 5hmC CpG each for intermediate clones (8,975 CpGs in 2,616 chromatin accessible peaks) and distal clones (21,022 CpGs in 3,572 chromatin accessible peaks). Motif enrichment analysis found 409 transcription factors (TF) signi cantly associated with high 5hmC chromatin accessible peaks in intermediate clones compared to 29 TFs in distal clones under the FDR < 0.05 threshold (Fig.…”
Section: Characterization Of High 5hmc Cpg Locimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, stable late hEMT states have been linked with maximal metastatic potential and worse overall survival 55 . Undoubtedly, the hEMT state can be further subdivided into sub-states, as shown by Goetz et al 4 , Brown et al 56 and also by us in the tissue-specific analyses. The true number of EMT intermediate states is just beginning to be explored.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, stable late hEMT states have been linked with maximal metastatic potential and worse overall survival 55 , explaining the variable metastatic potential we observed in cell lines in the context of hEMT. Undoubtedly, the hEMT state can be further subdivided into sub-states, as shown by Goetz et al 4 , Brown et al 56 and also by us in the tissue-specific analyses. The true number of EMT intermediate states is just beginning to be explored.…”
Section: Discussionmentioning
confidence: 75%